2009
DOI: 10.1002/ptr.3011
|View full text |Cite
|
Sign up to set email alerts
|

Effect of crocus sativus L. (saffron) stigma and its constituents, crocin and safranal, on morphine withdrawal syndrome in mice

Abstract: Crocus sativus L. has been shown to interact with the opioid system. Thus, the effects of aqueous and ethanolic extracts of stigma and its constituents were evaluated on morphine-withdrawal syndrome in mice. Dependence was induced using subcutaneous (s.c.) injections of morphine for 3 days. On day 4, morphine was injected 0.5 h prior the interaperitoneal (i.p.) injections of the extracts, crocin, safranal, clonidine (0.3 mg/kg) or normal saline. Naloxone was injected (5 mg/kg i.p.) 2 h after the final dose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 79 publications
(54 citation statements)
references
References 24 publications
1
53
0
Order By: Relevance
“…Crocin is the active ingredient in saffron, a natural spice commonly used in northern Indian and Persian cooking (65), and has been shown to prevent TNF-a-induced cell death of neuronally differentiated PC-12 cells (50). Crocin also diminishes free radical-induced stress, evidenced by the suppression of NO and malondialdehyde, in the brain after cerebral ischemia (52).…”
Section: Discussionmentioning
confidence: 99%
“…Crocin is the active ingredient in saffron, a natural spice commonly used in northern Indian and Persian cooking (65), and has been shown to prevent TNF-a-induced cell death of neuronally differentiated PC-12 cells (50). Crocin also diminishes free radical-induced stress, evidenced by the suppression of NO and malondialdehyde, in the brain after cerebral ischemia (52).…”
Section: Discussionmentioning
confidence: 99%
“…[50,51] More specifically, Imenshahidi et al reported that pretreatment of mice with intraperitoneal injection of crocin at a dose of 600 mg/kg for 4 days and 30 min before morphine administration, blocked the acquisition of morphine conditioned place preference (CPP). [51] Similarly, Hosseinzadeh and Jahanian have shown that both aqueous and higher doses of ethanolic saffron extracts suppressed morphine withdrawal syndrome in mice by reducing the number of jumping episodes.…”
Section: Morphine Withdrawal Syndromementioning
confidence: 99%
“…Interestingly, they also reported that the inhibitory effect of crocin alone on locomotor parameters was significantly lower than that of the aqueous extract, indicating a more specific effect of crocin on opioid system with reduced adverse effect rate. [50] Learning and memory effects: impact on Alzheimer's and Parkinson's diseases Concerning spatial cognitive abilities after chronic cerebral hypoperfusion, the administration of saffron extract or crocin solution significantly improved memory skills in rats compared with controls. [52] Several studies have been published by Abe's Research Group indicating the favourable effect of saffron extract, crocin and crocetin on memory and learning skills, in ethanol-induced learning behaviour impairments in swine.…”
Section: Morphine Withdrawal Syndromementioning
confidence: 99%
“…In addition, there was an ameliorative change with saffron extract and honey syrup against AlCl 3 neurotoxicity. The obtained molecular results suggested that AlCl 3 made induction for BCL-W gene, which was an anticancer gene or belonged to the DNA repair system in the brain cells, as well as for R-spondin and inositol polyphosphate 4-phosphatase genes, which helped in cell proliferation [113].…”
Section: Stmentioning
confidence: 96%